High intensity focused ultrasound for the treatment of solid tumors: a pilot study in canine cancer patients. (31st December 2022) - Carroll, Jennifer; Coutermarsh-Ott, Sheryl; Klahn, Shawna L.; Tuohy, Joanne; Barry, Sabrina L.; Allen, Irving C.; Hay, Alayna N.; Ruth, Jeffrey; Dervisis, Nick
Abstract: Purpose: To investigate the safety, feasibility, and outcomes of High-Intensity Focused Ultrasound (HIFU) for the treatment of solid tumors in a spontaneous canine cancer model. Methods: Dogs diagnosed with subcutaneous solid tumors were recruited, staged and pretreatment biopsies were obtained. A single HIFU treatment was delivered to result in partial tumor ablation using a commercially available HIFU unit. Tumors were resected 3–6 days post HIFU and samples obtained for histopathology and immunohistochemistry. Total RNA was isolated from paired pre and post treated FFPE tumor samples, and quantitative gene expression analysis was performed using the nCounter Canine IO Panel. Results: A total of 20 dogs diagnosed with solid tumors were recruited and treated in the study. Tumors treated included Soft Tissue Sarcoma ( n  = 15), Mast Cell Tumor ( n  = 3), Osteosarcoma ( n  = 1), and Thyroid Carcinoma ( n  = 1). HIFU was well tolerated with only 1 dog experiencing a clinically significant adverse event. Pathology confirmed the presence of complete tissue ablation at the HIFU targeted site and immunohistochemistry indicated immune cell infiltration at the treated/untreated tumor border. Quantitative gene expression analysis indicated that 28 genes associated with T-cell activation were differentially expressed post-HIFU. Conclusions: HIFU appears to be safe and feasible for the treatment of subcutaneous canine solid tumors, resulting in ablation of the targeted tissue. HIFU induced immunostimulatory changes, highlighting the canine cancer patient as an attractive model for studying the effects of focal ablation therapies on the tumor microenvironment.